Utilization of HEC DSS and HEC SSP Software for Rainfall Frequency Analysis in Drainage System Design for City’s Industrial Area - Rahayu, Diana; Rizal, Risdiamon; Chumaedi, Irpan (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
The analysis of designed rainfall frequency is a key input in various designing in the field of hydraulic engineering, such as floodplain mitigation, water structure construction, and flood inundation mapping. The calculation of rainfall frequency analysis still largely uses Microsoft Excel-based statistics that are calculated manually. The purpose of writing this article is to utilize HEC DSS and HEC SSP software in analyzing rainfall frequency at the measurement location. Measured rainfall data collected from the BMKG Hang Nadim rain station over the past 12 years has been inventoried in the HEC DSS and descriptions have been inputted in sections A to F. Then the data that has been input into HEC DSS will be integrated with HEC SSP. By plotting rainfall data at HEC SSP and running an analysis of the rainfall data, the rainfall frequency analysis at the measurement location was obtained. From running the HEC SSP with Normal, Log-Normal, Gumbel, and Log-Pearson III rainfall distributions, the distribution fit tests using the Kolmogorov-Smirnov method yielded the smallest error value for Log-Pearson III at 0.149 and for the Anderson-Darling method at 0.176. Therefore, the rainfall frequency analysis used is based on the Log-Pearson III rainfall distribution. Where the rainfall design values for return periods of 2, 5, 10, 20, and 50 years are sequentially 118.434 mm/day, 172.94 mm/day, 217.94 mm/day, 268.73 mm/day, 355.81 mm/day, and 442.90 mm/day. The rainfall frequency analysis results are used as input data to compute the flood discharge recurrence interval with the Rational methode. Using a flood discharge with a 10-year return period (Q10) and a concrete channel, the proposed drainage channel dimensions of 0.80 m and 1.20 m were determined.